Comparison of fresh and frozen thawed embryo transfer in terms of clinical pregnancy rate - Anitha, Adaboina; Rani, Burri Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In a standard IVF (in-vivo fertilization) procedure, the embryos formed after the fertilization of male and female gametes are allowed to grow for 3-5 days and then transferred back to the uterine cavity of the female, where they might get attached and start to grow. Objective of this study was to compare clinical pregnancy rate of fresh embryo transfers and frozen-thawed embryo transfers. Methods: This is a retrospective case control study in patients undergoing IVF /ICSI cycles from January 2018 to December 2018 were enrolled in assisted reproduction. Total of 200 women which contains 118 fresh embryo transfers and 82 frozen-thawed embryo transfers are studied. Results: Clinical pregnancy rates of fresh cleavage-stage embryo transfers compared with frozen-thawed cleavage-stage embryo transfers, were (53.3% versus 39.6%). Ectopic pregnancy is also significant in comparison. In patients under 35 years of ages and (57.1% versus 12.5%). In patients older than 35 years old, respectively. The multiple pregnancy rates, abortion rates and ectopic pregnancy rates did not differ significantly among the groups. Multiple pregnancy rate and abortion rate is significantly high in frozen-thawed blastocyst transfer than fresh embryo transfer. Whereas the ectopic pregnancy rates had no difference in both groups. Conclusions: The clinical pregnancy rates in fresh embryo transfer is high than that of frozen-thawed blastocyst.